Implementation of genomic medicine in a health care delivery system: A value proposition?. Issue 1 (11th March 2014) - Wade, Joanne E.; Ledbetter, David H.; Williams, Marc S.; Williams, Marc S.
<x xml:space="preserve">Abstract</x> The United States health care system is undergoing significant change and is seeking innovations in care delivery and reimbursement models that will lead to improved value for patients, providers, payers, and employers. Genomic medicine has the potential to be a disruptive innovation that if implemented intelligently can improve value. The article presents the perspective of the leaders of a large integrated healthcare delivery system regarding the decision to invest in implementation of genomic medicine. © 2014 Wiley Periodicals, Inc.